Introduction to manufacturing processes - Schey, John A. (McGraw-Hill, 2000)
This revision aims to address changes that have taken effect since the publication of the second edition. The most significant change has been in the attitude of industry to concurrent engineering. In 1987, mostly lip service was paid to it; today, it has become general practice in most competitive corporations. In the second edition , the author discussed this as the manufacturing system. In the third edition it becomes the focal point. Concurrent engineering involves the whole product realization process, including product concept, performance criteria, mechanical design and analysis, materials selection, process planning and modeling, production control, automation, assembly, management, and others. An introductory text cannot possibly cover all of these topics, hence the emphasis of the third edition remains on the physical principles and the application of these principles to processes. The major difference relative to the second edition will be the emphasis on interactions between process and design. Capabilities and limitations of processes will be highlighted to show what they mean in terms of design possibilities, and design modifications will be suggested for ease of manufacture. Impact on the environment and possibilities for recycling will be woven into the entire text.